A new hybrid differential evolution algorithm for the selection of optimal machining parameters in milling operations - Yildiz, Ali R. (Applied soft computing, 2013)
[Display omitted] ► A new optimization method (HRDE)based on differential evolution algorithm and receptor editing property of immune algorithm isdeveloped. ► The HRDE is applied to the manufacturing optimization problems. ► The HRDEgives an effective way to select optimal machining parameters in milling operations. This paper presents a novel hybrid optimization approach based on differential evolution algorithm and receptor editing property of immune system. The purpose of the present research is to develop a new optimization approach to solve optimization problems in the manufacturing industry. The proposed hybrid approach is applied to a case study for milling operations to show its effectiveness in machining operations. The results of the hybrid approach for the case study are compared with those of hybrid particle swarm algorithm, ant colony algorithm, immune algorithm, hybrid immune algorithm, genetic algorithm, feasible direction method and handbook recommendation.